2020
DOI: 10.1016/j.ajodo.2020.04.019
|View full text |Cite
|
Sign up to set email alerts
|

The National Dental Practice-Based Research Network Adult Anterior Open Bite Study: Patient satisfaction with treatment

Abstract: Introduction: This paper evaluates patient satisfaction of adults, who received orthodontic treatment for anterior openbite malocclusion across the United States. The factors that influence the satisfaction of these patients are also described. Methods: Practitioners were recruited from the National Dental Practice-Based Research Network. Upon joining the Network, practitioner demographics and information on their practices were acquired. Practitioners enrolled their adult patients in active treatment for ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The need of patients to increase their oral quality of life may be related to their need for orthodontic treatment for their malocclusion. Adult orthodontic patients who have received treatment to correct anterior open bite describe satisfaction with their treatment [ 41 ]. Analysis of the influence of having an anterior open bite on OHRQoL provides further insight into the need for orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The need of patients to increase their oral quality of life may be related to their need for orthodontic treatment for their malocclusion. Adult orthodontic patients who have received treatment to correct anterior open bite describe satisfaction with their treatment [ 41 ]. Analysis of the influence of having an anterior open bite on OHRQoL provides further insight into the need for orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most extensive prospective clinical studies in orthodontics (the National Anterior Open Bite Study) was conducted through the network during the 2012 to 2019 funding cycle. [3][4][5][6] A total of 347 adult subjects (with a diagnosis of anterior open bite) drawn from 91 practitioners throughout the United States were enrolled in the study. The study was completed successfully and provided valuable information on different treatment strategies, biomechanical approaches, end-of-treatment outcomes, patient/practitioner satisfaction, treatment success, and long-term stability of orthodontic correction of anterior open bites.…”
Section: Relevance Of Practice-based Research In the Current Landscapementioning
confidence: 99%
“…The study was completed successfully and provided valuable information on different treatment strategies, biomechanical approaches, end-of-treatment outcomes, patient/practitioner satisfaction, treatment success, and long-term stability of orthodontic correction of anterior open bites. [3][4][5][6] The study identified practice patterns that are in vogue nationally. The study was seamlessly conducted in private offices and academic centers with minimal impact on daily practice activities.…”
Section: Relevance Of Practice-based Research In the Current Landscapementioning
confidence: 99%
“…Finally resulting in satisfaction; as evaluated in national dental practice-based research from the United States. 2 The scope of Clear Aligner Therapy (CAT) has greatly increased over the past decade or so from treating merely a mild to moderate crowding to a well-controlled sophisticated therapeutic solution for complex malocclusions too. Though scholarly evidence for the system is still in infancy, 3,4 published case reports have showcased extremely encouraging outcomes with complex cases.…”
Section: Introductionmentioning
confidence: 99%
“…Finally resulting in satisfaction; as evaluated in national dental practice‐based research from the United States. 2 …”
Section: Introductionmentioning
confidence: 99%